Aspect Based Sentiment Analysis with Text Compression - Apoorva, T; Pradeep, N (International Journal of Computer Sciences and Engineering, 2025)
Sentiment Analysis measures the aptitude of people’s opinions through Natural Language Processing, Computational Lingus tics and Text analysis, which are used to extract and analyse subjectivity of information. This paper focuses on Aspect Based Sentiment Analysis, where Text Compression is performed before Aspect Based analysis. For a given huge text is compressed using Text compression model, which is considered as pre-processing task for Aspect Based Sentiment Analysis.